2020
DOI: 10.3390/life10080127
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Clinical Characteristics of Children and Adolescents with Metabolically Healthy Obesity: Role of Insulin Sensitivity

Abstract: Obesity represents a major risk factor for metabolic disorders, but some individuals, “metabolically healthy” (MHO), show less clinical evidence of these complications, in contrast to “metabolically unhealthy” (MUO) individuals. The aim of this cross-sectional study is to assess the prevalence of the MHO phenotype in a cohort of 246 overweight/obese Italian children and adolescents, and to evaluate their characteristics and the role of insulin resistance. Homeostasis model assessment–insulin resistance (HOMA-I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 58 publications
1
6
0
Order By: Relevance
“…Although the hyperinsulinemic-euglycemic clamp is considered the gold standard for the identification of insulin resistance, due to its complexity and invasiveness, the most widespread method for assessing insulin resistance among children is through the calculation of HOMA-IR. Studies have found that children with MHO phenotype had lower HOMA-IR index as compared to children with MUO phenotype ( 13 , 29 , 31 , 37 , 38 ), however we did not observe this trend and our finding agrees with other more recent studies ( 39 , 40 ). A study found that both children with MHO and MUO phenotype had significantly higher HOMA-IR when compared to normal weight peers indicating that a state of insulin resistance was already present ( 40 ).…”
Section: Discussionsupporting
confidence: 78%
“…Although the hyperinsulinemic-euglycemic clamp is considered the gold standard for the identification of insulin resistance, due to its complexity and invasiveness, the most widespread method for assessing insulin resistance among children is through the calculation of HOMA-IR. Studies have found that children with MHO phenotype had lower HOMA-IR index as compared to children with MUO phenotype ( 13 , 29 , 31 , 37 , 38 ), however we did not observe this trend and our finding agrees with other more recent studies ( 39 , 40 ). A study found that both children with MHO and MUO phenotype had significantly higher HOMA-IR when compared to normal weight peers indicating that a state of insulin resistance was already present ( 40 ).…”
Section: Discussionsupporting
confidence: 78%
“…At this moment, obesity is described as a heterogeneous syndrome (determined by the genetic and environmental factors' interaction) [8,[12][13][14]. Previous studies have pointed out the different obesity types [15]: "metabolically healthy obesity"-MHO (defined by obesity presence without metabolic disturbance or metabolic syndrome features [8,12,16] and "metabolically unhealthy obesity-MUO" [8,12,16].…”
Section: Introductionmentioning
confidence: 99%
“…The proportions of low-grade inflammation were similar to the adolescents with MetS defined by traditional definition. 30 These adolescents have an adverse status of insulin resistance and low-grade inflammation. So it may be suitable for considering these adolescents as MetS and giving early intervention.…”
Section: Discussionmentioning
confidence: 99%